The genomic landscape of sensitivity to arsenic trioxide uncovered by genome-wide CRISPR-Cas9 screening - Chen, Jun-Zhu; Wang, Li-Na; Luo, Xue-Qun; Tang, Yan-Lai (Frontiers in Oncology, 2023)
Arsenic trioxide (ATO) is a promising anticancer drug for hematological malignancy. Given the dramatic efficacy of acute promyelocytic leukemia (APL), ATO has been utilized in other types of cancers, including solid tumors. Unfortunately, the results were not comparable to the effects on APL, and the resistance mechanism has not been clarified yet. In this study, we performed a genome-wide CRISPR-Cas9 screening to provide a landscape of genomic perturbations in response to ATO. We identified KEAP1 as the top gene relating to ATO resistance. Besides, we applied enrichment analysis and identified vital ATO-related pathways such as metabolism, chemokines and cytokines production and signaling, and immune system responses. These integrated results provided new insights into the pharmacological mechanism of ATO and potentiate for further applications in cancer treatments.